Hábito alimentar e morfologia do aparelho digestivo de espécies de Carabidae (Insecta: Coleoptera) associados a plantas herbáceas e ao algodoeiro colorido - Matta, Danilo Henrique da [UNESP] (2014)
The Carabidae beetles (Coleoptera) have great importance to agriculture as natural enemies of insect pests. However, little is known about the content of these beetles feed. This study aimed to assess the occurrence and feeding habits of Carabid species associated with herbaceous plants (PHF) in different growth periods of coloured cotton. The food contents was evaluated in species that occurred in coloured cotton, Gossypium hirsutum L. latifolium Hutch., variety BRS green, herbaceous cotton, adjacent weeds and PHF Lobularia maritima (L.), Tagetes erecta L., Fagopyrum esculentum Moench. Some species of Carabid beetles occurred at different cotton growth periods and the highest number of individuals was found in the cotton reproductive stage. The results showed many types of feed contents ingested by the Carabidae beetles gut tract, like arthropods and vegetable associated with PHF in different growth periods of cotton and can be considered polyphagous predators. The gut tract morphology showed that nine species of Carabid beetles showed standards structures adapted to the type of diet ingested